Following others through an information maze: The impact of social navigation on information seeking behavior. Issue 124 (April 2019) - Farzan, Rosta; Brusilovsky, Peter
Abstract: "Social Navigation" for the Web has been created in response to the problem of disorientation in an information space. It helps users tackle the information overload challenge by visualizing the traces of behavior of other users and adding social affordances to the information space. Despite the popularity of the concept of social navigation, very few studies of information systems with social navigation can be found in the research literature. In this paper, we report on our study of the impact of social navigation support in the context of task-centered information access. We explore the design of our information access interface which is designed to offer integrated social navigation support, as well as our experiment to systematically assess how social navigation support influenced participants' information seeking behavior. This experiment will identify situations in which social navigation support is most useful and to investigate the effect of interpersonal trust as an individual factor on the likelihood of following social navigation cues. The results of the study show that social navigation support can successfully guide participants to relevant documents, enabling them to achieve higher search performance. The study also revealed that the effect of social navigation cues on participants' information seeking behaviors varies under different circumstances, especially under time constraints and for those with high levels of interpersonal trust.